Recent advancements in graph theory - Shrimali, N. P.; Shah, Nita H. (Boca Raton, FL : CRC Press, 2020)
"Graph Theory is a branch of discrete mathematics. It has many applications to many different areas of Science and Engineering. This book provides the most up-to-date research findings and applications in Graph Theory. This book focuses on the latest research in Graph Theory. It provides recent findings that are occurring in the field, offers insights on an international and transnational levels, identifies the gaps in the results, and includes forthcoming international studies and research, along with its applications in Networking, Computer Science, Chemistry, and Biological Sciences, etc. The book is written with researchers and post graduate students in mind"--
OCLC-licensed vendor bibliographic record.
Keywords: Graph theory; Discrete mathematics; COMPUTERS / Operating Systems / General; MATHEMATICS / Combinatorics; MATHEMATICS / Probability & Statistics / General